The Analysis of Students' Listening Proficiency and Their Motivation in (Meta)-Cognitive Collaboration Strategy Instruction - Dodi Mulyadi (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Students motivation is important in mastering English especially in mastering listening skill. The aim of the study is to find out the students listening proficiency viewed from their motivation. Quantitative analysis was used to investigate the findings of this research by using pre-test post-test one group design. The research aims at finding the results of students listening proficiency viewed from their motivation after they have been treated by using M-CCSI as (meta)-cognitive collaboration strategy instruction. The instruments of the research are TOEFL Test of listening section and Motivation questionnaire. The participants of study 28 EFL students from one class at Muria University of Kudus (UMK) the 3 semester of year 2016-2017.After analyzing the improvement of delta score, the students who have low motivation has 5.81 of gain score after doing treatment by using M-CSSI. Meanwhile, the students who have high motivation have a gain score 6.75.The results shows that the students motivation do not influence significantly with p value 0.493 which is above the 5% of significant level.